Best Paper Selection (Yearbook of Medical Informatics, 2017)
Althoff, T, Clark K, Leskovec, J. Large-scale Analysis of Counseling Conversations: An Application of Natural Language Processing to Mental Health. Trans Assoc Comput Linguist 2016(4):463-76 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5361062/Kilicoglu, H, Demner-Fushman, D. Bio-SCoRes: A Smorgasbord Architecture for Coreference Resolution in Biomedical Text. PLoS One. 2016 Mar 2;11(3):e0148538 http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0148538Morid, MA, Fiszman, M, Raja, K, Jonnalagadda, SR, Del Fiol, G. Classification of clinically useful sentences in clinical evidence resources. J Biomed Inform. 2016 Apr;60:14-22 http://www.sciencedirect.com/science/article/pii/S1532046416000046?via%3DihubShivade C, de Marneffe MC, Fosler-Lussier E, Lai AM. Identification, characterization, and grounding of gradable terms in clinical text. Proceedings of the 15th Workshop on Biomedical Natural Language Processing. 2016:17-26 https://www.semanticscholar.org/paper/Identification-characterization-and-grounding-of-g-Shivade-Marneffe/c00ba120de1964b444807255030741d199ba6e04Wu, Y, Denny, JC, Rosenbloom, ST, Miller, RA, Giuse, DA, Wang, L, Blanquicett, C, Soysal, E, Xu, J, Xu, H. A long journey to short abbreviations: developing an open-source framework for clinical abbreviation recognition and disambiguation (CARD). J Am Med Inform Assoc 2017 Apr 1;24(e1):e79-e86 https://academic.oup.com/jamia/article-abstract/24/e1/e79/2631496/A-long-journey-to-short-abbreviations-developing?redirectedFrom=fulltext